Adapting evidence-based group therapies following COVID-19 restrictions. (February 2022) - Dark, Frances; Miles, Anne; Madson, Kathy; Strochnetter, Ellen
Aim: The COVID-19 pandemic has created barriers to the running of group therapies due to the need to maintain social distance. This paper aims to describe modifications of existing therapeutic groups delivered to people diagnosed with serious and enduring mental illnesses (SMIs) to enable the therapies to continue in an online format due to the COVID-19 restrictions. Conclusions: Therapists and consumers were motivated to find a way to continue the therapies described despite the context of the restrictions imposed due to COVID-19. This paper describes what was involved in 'pivoting' to a new mode of practice and modifications that were required over time and as new regulations were put in place. Formal research is required to establish an evidence base if these therapies were required to be regularly delivered in an online mode.